Using language(s) to develop subject competences in CLIL-based practice - Ball, Phil (Pulso. Revista de educación, 2016)
This article documents and analyses the shift in emphasis that has taken place in CLIL and other forms of multilingual educational practice, where priorities seem to be placing a welcome importance on the use of language as a transversal element in the development of the range of subject competences that constitute the school curriculum. CLIL has also changed from being a methodology to help teachers support learner development in the particular discourse field of an academic subject to a more inclusive paradigm which has attracted the attention of languageteaching practitioners. The elusive notion of what constitutes ‘content’ is therefore more important to clear up than ever, since both subject and language teachers are concerned with its shape and its characteristics, and of understanding its distinct types. This article offers the idea of content as three-dimensional, of which language is a crucial component, arriving at the inevitable conclusion that language is the only true transversal element which unites the diversity of subject competences, just as long as its use remains subservient to procedural (competence-based) aims. This is the new single focus of CLIL